THE PREPOSITIONAL PHRASES AND THE SUBORDINATE CLAUSES IN “DAVID COPPERFIELD” BY CHARLES DICKENS: A STUDY OF SYNTAX - Gemi Salvianto; Muhammad Sulhan (INFERENCE: Journal of English Language Teaching, 2022)
The objectives of the research are to know the prepositional phrases and subordinate clauses in “David Copperfield” by Charles Dickens. The total sample data of this research are sixty each for two variables. The technique of collecting data of prepositional phrases and subordinate clauses is determining texts in the novel, collecting the selected sentences, and storing them in a table. The research methodology applied is qualitative, and the technique of data analysis is descriptive analysis and hierarchical structures of syntax. Three categories are used to analyze prepositional phrases: post-modifier of a noun (pN), post-modifier of an adjective (pAdj) and adverbial (pA) while to analyze the subordinate clauses, complement clauses (CC), adjunct or adverbial clauses (AC), and relative clauses (RC) are employed. The results of the research are: 1) Prepositional phrases that function as adverbial (pA) are found to be the most category used with 65%, and the preposition of is the most used among others with twelve times in total. 2) Subordinate clauses that function as adjunct clauses (AC) are found to be the most category used with 62%, and the subordinate conjunction when is the most used among others with eleven times in total.